A giant coronary artery aneurysm associated with multiple peripheral arterial aneurysms and an abdominal aortic aneurysm. (23rd February 2018) - Ahmadov, Kamran; Sologashvili, Tornike; Roffi, Marco; Huber, Christoph
Abstract: We report a rare association of a giant aneurysm of the left circumflex coronary artery with multiple peripheral arterial aneurysms and an abdominal aortic aneurysm in a 70-year-old patient. The exclusion of the giant circumflex artery aneurysm was performed successfully by proximal and distal ligation of all branches and bypass surgery using saphenous grafts to vascularize the distal circumflex artery and the marginal branch.